Conference: The 1st Annual Seminar of Experimental Archaeology in Norway - Tine Schenck (EXARC Journal)
The 2010 international symposium of the Austrian Society for Prehistory and Early History (ÖGUF) took place 27-30 October at The Museum for Natural History in Vienna under the patronage of State Captain and Mayor of Vienna Dr. Michael Häupl – and the general director of the Museum for Natural History Vienna, Univ.-Prof. Dr. Christian Köberl. Theme was experimental archaeology: theory, practice, science, education.